Racial/ethnic differences in healthcare use among patients with uncontrolled and controlled diabetes. Issue 3 (3rd April 2019) - Taylor, Yhenneko J.; Spencer, Melanie D.; Mahabaleshwarkar, Rohan; Ludden, Thomas
ABSTRACT: Objectives: To examine racial/ethnic differences in healthcare use among patients classified as having controlled and uncontrolled diabetes. Design: Data from the Carolinas HealthCare System electronic data warehouse were used. Glycemic control was defined as glycosylated hemoglobin (HbA1c) < 8% (64 mmol/mol) in 2012 ( n = 9996). Patients with HbA1c ≥ 8% (64 mmol/mol) in 2012 were classified as uncontrolled ( n = 2576). Race and ethnicity were jointly classified as non-Hispanic Black, non-Hispanic White or Other. Separate mixed effects negative binomial models estimated the independent effect of race/ethnicity on the number of emergency department (ED) visits, hospitalizations and physician office visits in 2013, in each patient group, adjusting for significant confounding variables. Results: Rates of diabetes-related ED visits were two to three times higher for non-Hispanic Blacks compared to non-Hispanic Whites (uncontrolled rate ratio [RR]: 3.41 95% CI: 1.41–8.22; controlled RR: 2.95; 95% CI: 1.78–4.91). Similar differences were observed for all-cause ED visits (uncontrolled RR: 1.83, 95% CI: 1.50–2.24; controlled RR: 2.45, 95% CI: 2.17–2.77). Non-Hispanic Blacks with controlled and uncontrolled diabetes also had lower rates of all-cause physician office visits when compared to non-Hispanic Whites (uncontrolled RR: 0.84, 95% CI: 0.77–0.91; controlled RR: 0.81, 95% CI: 0.78–0.84). Conclusion: Notable racial/ethnic disparities exist in the use of emergency services and physician offices for diabetes care. Strategies such as patient education and care delivery changes that address healthcare access issues in racial/ethnic minorities should be considered to offer better diabetes management and address diabetes disparities.